2017
DOI: 10.1002/jrs.5150
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman analysis on the combined use of ammonium oxalate and ammonium phosphate for the consolidation and protection of carbonate stone artifacts

Abstract: Ammonium oxalate ((NH4)2C2O4, AmOx) and more recently di‐ammonium phosphate ((NH4)2HPO4, DAP) are used as inorganic agents in the conservation of cultural heritage for protection and consolidation of carbonate stone artifacts. In this work, we carry out a Raman investigation on the extent of penetration provided by a combined use of them. In particular, AmOx followed by DAP, DAP followed by AmOx, and a DAP + AmOx mixture are applied on tablets of pure CaCO3 as well as on degraded marble samples. Then, cross‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Such mechanical improvement is notable, considering that in a previous study we found the consolidating ability of the ammonium oxalate treatment to be very modest [29]. The poor consolidating behaviour of ammonium oxalate was ascribed to the reduced depth of formation of whewellite [29], owing to the very rapid reaction between the ammonium oxalate solution and calcite [54]. In addition to the different thickness of samples to be consolidated (1 cm in the present case, 2 cm in the previous case [29], a possible explanation for the better results obtained in this study may be the different application technique.…”
Section: Consolidating Abilitymentioning
confidence: 71%
“…Such mechanical improvement is notable, considering that in a previous study we found the consolidating ability of the ammonium oxalate treatment to be very modest [29]. The poor consolidating behaviour of ammonium oxalate was ascribed to the reduced depth of formation of whewellite [29], owing to the very rapid reaction between the ammonium oxalate solution and calcite [54]. In addition to the different thickness of samples to be consolidated (1 cm in the present case, 2 cm in the previous case [29], a possible explanation for the better results obtained in this study may be the different application technique.…”
Section: Consolidating Abilitymentioning
confidence: 71%
“…Osticioli et al employed micro‐Raman analysis to study the combined use of ammonium oxalate and ammonium phosphate for the consolidation and protection of carbonate stone artifacts. Their discussion took into consideration several aspects including solubility and interaction dynamics between reaction products, as well as the peculiar morphological features of the artifact, which are shown to play a significant role in treatment choice . Rousaki et al described the first use of portable Raman instrumentation for the in situ study of prehistoric rock paintings in Patagonian sites.…”
Section: Art and Archaeologymentioning
confidence: 99%
“…Their discussion took into consideration several aspects including solubility and interaction dynamics between reaction products, as well as the peculiar morphological features of the artifact, which are shown to play a significant role in treatment choice. [125] Rousaki et al described the first use of portable Raman instrumentation for the in situ study of prehistoric rock paintings in Patagonian sites. During a single research campaign, 16 shelters and one cave were investigated, which makes this study as one of the most condensed expeditions on measuring rock art paintings.…”
Section: Other Coherent Nonlinear Techniquesmentioning
confidence: 99%
“…Nanosilica formulations have been proposed as promising treatments, even though compatibility, depth of penetration, durability, and other variables are still being evaluated [11,12]. Nanostructured materials represent the most advanced frontier of the inorganic approach to the consolidation of carbonate stones, which were thoroughly investigated along the last decades using various treatments based on barium hydroxide, ammonium oxalate (AmOx), and more recently, di-ammonium phosphate (DAP) [13][14][15][16]. Regardless to their well-known limitations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a multianalytical approach based on XRD, FTIR, TGA techniques and SEM micrographs has been successfully adopted for monitoring compositional and microstructural evolutions of powdery archaeological limestone surfaces upon DAP treatment followed by in-situ precipitation of HAP [20]. Likewise, a Raman investigation on the extent of penetration provided by a combined use of AmOx and DAP has been carried out on tablets of pure CaCO3 as well as on deteriorated marble samples [16]. The results have demonstrated greater penetration depth (down to 2.5 mm) and hence better bulk consolidating properties of DAP with respect of AmOx.…”
Section: Introductionmentioning
confidence: 99%